Machine learning classifiers for android malware analysis (2016)
Android is an operating system which currently has over one billion active users for all their mobile devices, with a market impact that is influencing an increase in the amount of information that can be obtained from different users, facts that have motivated the development of malware by cybercriminals. To solve the problems caused by malware, Android implements a different architecture and security controls, such as unique user ID (UID) for each application, system permissions, and its distribution platform Google Play. It has been shown that there are ways to violate that protection, and how the complexity for create a new solutions are increased while cybercriminals improve their skills to develop malware.